THE IMPACT OF PRODUCT DESCRIPTION OF INVOLVEMENT PLATFORM TOWARDS PURCHASE INTENTION AT ONLINE STORES ON THE MARKETPLACE PLATFORM - Immanuel, Dewi Mustikasari; Peter, Yosef (Jurnal Aplikasi Manajemen, 2022)
This quantitative method research aims to determine whether the product description influences purchase intention, with the mediation of enduring and situational involvement as part of platform involvement. This research is based on the Theory of Planned Behavior (TPB), Involvement theory, and previous research on product description, platform involvement, and purchase intention on online platforms. The number of samples in this study was 95 respondents, with the determination of the sample using a purposive sampling technique, with the respondent’s criteria being online consumers who had made transactions on the Tokopedia and Shopee marketplace platforms. The data analysis method is structural equation modelling Partial Least Square (SEM-PLS) with SmartPLS 3.3.7 software. The results of this study indicate that product description can positively and significantly affect enduring and situational involvement. However, the mediation between the product description and purchase intention is only fully found on the situational involvement variable, while enduring involvement does not affect purchase intention. It is different from the results of previous studies, which stated that enduring and situational involvement influence purchase intention. The implications for further researchers, it is recommended to reuse enduring involvement and purchase intention variables and other variables that can lead to enduring involvement concerning consumer purchase intention. Different types of products, populations, and analytical models, can be used to conduct further research to provide a more complete and appropriate description and data.